2018
DOI: 10.1101/401406
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age of onset in genetic prion disease and the design of preventive clinical trials

Abstract: Regulatory agencies worldwide have adopted programs to facilitate drug development for diseases where the traditional approach of a randomized trial with a clinical endpoint is expected to be prohibitively lengthy or difficult. Here we provide quantitative evidence that this criterion is met for the prevention of genetic prion disease. We assemble age of onset or death data from N=1,094 individuals with high penetrance mutations in the prion protein gene (PRNP), generate survival and hazard curves, and estimat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 133 publications
0
19
0
Order By: Relevance
“…Additionally, some of the residues that were identified by our simulations as relevant to the stability of the dimers were reported as involved in disease-associated mutations (Tables 2 and ST1) [9] , although some of these mutations may be benign, low risk or have low penetrance [11,13] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, some of the residues that were identified by our simulations as relevant to the stability of the dimers were reported as involved in disease-associated mutations (Tables 2 and ST1) [9] , although some of these mutations may be benign, low risk or have low penetrance [11,13] .…”
Section: Resultsmentioning
confidence: 99%
“…The four main subtypes of prion disease in humans are correlated with different patterns of PrP Sc toxicity in the brain: Creutzfeldt-Jakob Disease (CJD), Gerstmann-Sträussler-Scheinker (GSS) syndrome, Fatal Insomnia (FI) and Variably Protease-Sensitive Prionopathy (VPSPr) [7] . The risk of developing prion disease is influenced by PrP C polymorphisms and several mutations in the PrP gene [8][9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, our data indicate that mutant PrPs not only impair the trafficking and synaptic delivery of PrP-interacting cargoes, but also have a more general effect on protein transport, probably due to inappropriate activation of SFK-mediated signaling. Carriers of PRNP mutations do not manifest symptoms until adulthood ( 41 ), even though PrP is expressed from early embryogenesis and misfolded/aggregated mutant PrP starts accumulating early postnatally in the CNS, as inferred from studies in mice ( 3 , 19 , 42 , 43 , 44 ). This suggests that disease ensues when a critical toxic threshold is reached ( 45 , 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Observation of iatrogenic CJD has shown that the incubation time in prion diseases may take up to four decades [11]. A recent multinational study provided data on the age of onset in the three most common mutations and observed median ages of 53 years (D178N), 56 years (P102L), and 62 (E200K) years with a huge variability ranging from 12 to 92 years [6]. These data may help to decide when advanced biomarker analyses to investigate study eligibility should be performed.…”
Section: Genetic Prion Disease As An Opportunity For Pre-clinical Interventionsmentioning
confidence: 99%
“…• accurate diagnosis is challenging, especially in early disease stages • rapid disease progression and poor clinical condition may cause legal representatives either to reject any treatment or to assure medication (in case of easily available drugs, e.g. Doxycycline) • low case numbers require alternative and innovative study designs as well as statistical methods • noninvasive pre-clinical, stage-reflecting, and predictive biomarkers were not available in the past The information in Table 1 reflect the authors' clinical and research experience, as well as data from the literature [4][5][6].…”
Section: Identification Of Eligible Individuals Trial Execution and Data Analysesmentioning
confidence: 99%